2015
DOI: 10.1038/onc.2015.443
|View full text |Cite
|
Sign up to set email alerts
|

ASXL2 promotes proliferation of breast cancer cells by linking ERα to histone methylation

Abstract: Estrogen receptor alpha (ERα) has a pivotal role in breast carcinogenesis by associating with various cellular factors. Selective expression of additional sex comb-like 2 (ASXL2) in ERα-positive breast cancer cells prompted us to investigate its role in chromatin modification required for ERα activation and breast carcinogenesis. Here, we observed that ASXL2 interacts with ligand E2-bound ERα and mediates ERα activation. Chromatin immunoprecipitation-sequencing analysis supports a positive role of ASXL2 at ERα… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 52 publications
0
48
0
Order By: Relevance
“…Recent work has suggested that the plant homeofinger domain (PHD) of ASXL2 may bind to and influence monomethylation at H3K4 (ref. 55), a mark associated with functional enhancers565758. This potential function of the ASXL2 PHD domain may provide a mechanistic explanation for the observation here of alterations of enhancers with loss of ASXL2.…”
Section: Discussionmentioning
confidence: 68%
“…Recent work has suggested that the plant homeofinger domain (PHD) of ASXL2 may bind to and influence monomethylation at H3K4 (ref. 55), a mark associated with functional enhancers565758. This potential function of the ASXL2 PHD domain may provide a mechanistic explanation for the observation here of alterations of enhancers with loss of ASXL2.…”
Section: Discussionmentioning
confidence: 68%
“…3 and 4), each of which have been recently shown to bind to BAP1 (Sahtoe et al 2016). The ASXM1 and ASXM2 domains of ASXL proteins have been reported to bind to several nuclear hormone receptors (NHRs), including the androgen receptor (Grasso et al 2012), estrogen receptor (Park et al 2015), and PPARγ (Park et al 2011). …”
Section: Discovery Of the Mammalian Asxl Gene Familymentioning
confidence: 99%
“…For example, although phylogenetic analyses suggest that the PHD domain of ASXL proteins may bind histone H3 lysine 4 trimethyl (H3K4me3) (Aravind and Iyer 2012; Katoh 2015), the function of the carboxy-terminal PHD domain of ASXL proteins is in need of definition. One recent report revealed that the PHD domain of ASXL2 binds H3K4me1 and H3K4me2, but validation of this finding with quantitative measurement of binding affinity and other confirmatory assays was not performed nor were the functions of ASXL1 or ASXL3 PHD domains studied (Park et al 2015). Moreover, the possibility that the ASXL PHD domains may bind to nonhistone proteins remains to be tested.…”
Section: Discovery Of the Mammalian Asxl Gene Familymentioning
confidence: 99%
“…The present meta-analysis identified 22 potential secreted biomarkers, of which CXCL16 and CXCL8 have been previously reported as biomarkers in patients with Crohn's disease (87) and in several diseases, including urinary bladder cancer, non-Hodgkin's lymphoma and pulmonary infections (88). A literature review indicated that CXCL8 is linked to autophagy in melanoma cell lines (35) and has been reported in metastasis (37). Here, CXCL8 appeared in the top 50 of modulated genes (Fig.…”
Section: Differential Expression Levelsmentioning
confidence: 63%